The way of a writer: taoism in Ursula K. Le Guin's The left hand of darkness - Pérez, Martín Gregorio (2003)
When I first started reading Ms. Le Guin's novel, I was struck by the presence in it of what I then recognized as elements from Eastern philosophy and thought, in particular Taoism. Long before mention is made of the yin-yang concept and symbol, in Chapter 19, I felt these elements formed an underlying, yet essential, basis for the understanding of the book. It was much later that I also learned about this writer's interest in Taoism as an explanation, a resource, an answer, and a choice, and about her consequent knowledge of the Tao Te Ching.